Proteolytic processing of pol-TYB proteins from the yeast retrotransposon Ty1. - Garfinkel, D J (1991)
Using antibodies directed against the TYB1 protein of the transpositionally competent retrotransposon Ty1-H3, we have identified three mature proteins of 23, 60, and 90 kDa and processing intermediates of 140 and 160 kDa that are derived from the 190-kDa TYA1-TYB1 polyprotein. Mature proteins and variable amounts of the precursors cofractionate with Ty viruslike particles. The map locations and precursor-product relationships of mature TYB1 polypeptides suggest that p23 is Ty1 protease, p90 is integrase, and p60 contains reverse transcriptase and RNase H. Immunoprecipitation and immunoblot analyses of Ty1 proteins show that p190 is cleaved to form p160. The p160 intermediate is cleaved to form p23 and p140, and p140 is cleaved to form p90 and p60. Processing of TYB1 proteins is dependent on Ty1 protease. Immunoblot analysis of TYB proteins from different Ty1 isolates reveal that correct processing of TYB1 proteins is a characteristic of functional Ty1 elements, whereas aberrant processing is a common defect found in transposition-incompetent elements.